Answer:
x=3 and y=-5
I eliminated the y variable so I found the least common factor between 2 and 3 which is 6. I multiplied the first equation by 2 and the second equation by -3 (it's a negative 3 because in order to eliminate the variable, they need to have opposite signs.) That gives me a result of:
4x-6y=42
-15x+6y=-75
Now you can eliminate the y variables and just add the equations together to get:
-11x=-33
x=3
Then plug the x back into one of the original equations to find your y.
2(3)-3y=21
6-3y=21
-3y=15
y=-5
Finally always check your answers by plugging them into the other equation that you did not use
5(3)-2(-5)=25
15+10=25
25=25
Hope this helps!